REDUCE RISK OF FINANCIAL STABILITY ENTERPRISE IN CURRENT CONDITIONS - E. Y. Fayantzeva (Стратегические решения и риск-менеджмент)
In the current economic conditions, characterized by high level of uncertainty, the need to achieve strategic financial goals of the company and ensuring its long-term financial stability is impossible without an effective system of strategic financial management, an integral part of which is a risk management strategy reduce financial stability. The author loss risk management strategy of financial stability, substantiated scientific and methodological tools of its creation, outlines the basic principles of implementation, performed updated list of the functions. In order to maximize approximation developed strategies to the needs of industrial enterprises and economic instability are highlighted and ordered typical violations of risk management process by the author. Generalizes the scheme proposed risk management strategy losing financial stability. Outlines the key steps in developing and implementing strategies under consideration with their detailed description.